Rubber seed: Its biological and industrial applications - Thomas Vinoth; Mercykutty V C; Saraswathyamma C K (Planter, 1998)
Rubber seeds are utilized primarily for raising root stock for the propagation of high yielding varieties through budding. Seeds collected from well maintained polyclonal garden are recommended as planting material especially ;in non-traditional rubber growing areas. Seed morphological characters are unique for clones and hence assume taxonomic significance. Oil and cake obtained from the rubber seed have commercial importance. Products derived from rubber seed oil (RSO) are used in paint industry for factice, for soft soap, in medicine as antimalarial oil, and in engineering as core binders. The study on the diesel engine performance test with RSO has been reported. Rubber seed cake has nutritive value and is being used in cattle and poultry feeds. Seed cake can also be used as good manure. The edibility of rubber seed has also been mentioned.
Keywords: Clone identification; Hevea brasiliensis; Industrial applications; Propagation; Rubber seed